PSYCHOANALYTIC CRITICISM ON MIZOGUCHI’S PERCEPTION OF THE GOLDEN TEMPLE IN THE TEMPLE OF THE GOLDEN PAVILION - Kobis, Dewi Christa; Dewi Christa Kobis (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
This paper is to discuss the psychological aspects in the novel which is written by Yukio Mishima entitled The Temple of the Golden Pavilion which is translated into English by Ivan Morris and published at the first time in English translation in 1959. The Temple of the Golden Pavilion is one of the literary products which were written by Yukio Mishima that got its popularity among readers around the world since it has been translated into English. The Temple of the Golden Pavilion has several important psychological aspects that might be important to be analyzed since the psychological aspects are necessary to comprehend deeper about how and why the heroin behaves like what is written in the novel.